Grammatical and Lexical Cohesion Analysis of Arabic Learning Videos on the Learn with Zakaria YouTube Channel - Feby Moch Febrian; Yusuf Ali Tantowi (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
The rapid growth of YouTube as a medium for Arabic language learning has raised the need to examine not only its functional aspects but also the linguistic quality of the verbal explanations it delivers, particularly how discourse coherence is constructed through cohesive devices. This study aims to analyze the types, forms, and functions of grammatical and lexical cohesion devices used in Arabic learning videos on the YouTube channel Learn with Zakaria. This research employed a descriptive qualitative method with a content analysis design. From a population of 27 eligible videos uploaded within one year, three representative videos were purposively selected and analyzed based on the cohesion categories proposed by Halliday and Hasan (1976). The findings revealed 308 cohesion devices, consisting of grammatical cohesion (reference and conjunction) and lexical cohesion (reiteration and collocation). Among these, personal reference, additive conjunction, and repetition emerged as the most frequently used cohesive devices, while substitution and ellipsis were not identified because the utterances tended to employ explicit rather than economical language forms to facilitate audience comprehension. In conclusion, the learning videos employ cohesion integratively to establish discourse unity through referential relationships, gradual addition of information, and vocabulary repetition to maintain topic focus. These findings contribute to the development of cohesion studies in digital Arabic learning media and provide practical implications for developing Arabic learning videos that are more communicative, systematic, and easier for learners to understand.